Fluoroalkyl and fluoroaryl fullerenes, polycyclic aromatic hydrocarbons, and copper(I) complexes: synthesis, structure, electrochemical, photophysical, and device properties - Reeves, Brian J., author; Strauss, Steven H., advisor; Shores, Matthew P., committee member; Rappé, Anthony K., committee member; McNally, Andrew, committee member; Ridley, John, committee member (Colorado State University. Libraries, 2020)
In many fields of research, ranging from materials chemistry to medicinal chemistry, understanding the structural, electrochemical, and photophysical properties of materials is essential to establishing trends and predicting usefulness and future performance. This work has focused on the impact of strongly electron withdrawing perfluoroaryl and perfluoroalkyl substituents on the properties of fullerenes, polycyclic aromatic hydrocarbons (PAHs), hetero-PAHs, and copper(I) complexes with the goal of establishing and understanding the fundamental reasons for any observed trends. In Chapter 1, the first successful example of vacuum-deposited organic photovoltaic cells (OPVs) based on a fullerene derivative and a small-molecule donor is reported. A series of thermally robust fluorous fullerene acceptors with experimental gas-phase electron affinities ranging from 2.8 to 3.3 eV are paired with new dicyanovinyl thiophene-based molecular donors to enable direct comparison of their performance in planar and bulk heterojunction architectures in cells fabricated by vacuum deposition. Unprecedented insights into the role of the acceptor intrinsic molecular and electronic structures are obtained, which are not obscured by solvent and additive effects as in the typical solution-processed fullerene-based OPVs. Additionally, the fullerene derivative, C60CF2, was utilized in vacuum-deposited organic field effect transistors (OFETs), and it was shown to have superior device lifetime compared to C60 based OFETs. In Chapter 2, a new synthesis of 9,10-bis(perfluorobenzyl)anthracene, a promising blue organic light emitting diode (OLED) material is reported. The yield was improved from 7% to 17%, while the separations conditions were improved to only require one stage of HPLC. In Chapters 3 and 4, the trifluoromethylation of two hetero-PAHs, phenanthroline and phenanthridine, is discussed. The structure, solid-state packing, and electronic properties of the products are examined. Previously unknown structure-property relationships were established between the electronic properties and the position of CF3 groups. Additionally, the synthesis and excited-state dynamics for a series of homoleptic copper(I) phenanthroline complexes with 2, 3, and 4 trifluoromethyl groups are reported. Surprisingly, the observed time-resolved dynamics and emission trend is that addition of trifluoromethyl groups past two decreases the excited state lifetime and increases excited-state distortion.
Keywords: organic electronics; PAH; perfluoroarylfullerene; organic photovoltaic; MLCT; perfluoroalkylfullerene